THE CORRELATION OF ADOLESCENT EMOTIONAL STABILITY TO ACADEMIC STRESS AT SMAN 3 TANGERANG REGENCY - Hidayati, Ika Apriliana Nur; Santoso , Abdul (Journal of Vocational Nursing, 2022)
Introduction: Stress is a disorder of the nervous system that can cause a fast heartbeat, sweaty body, flushed face and so on. Emotional stability is a person's ability to adapt to the surrounding environment. Factors that come from within themselves or internal factors are the low intellectual property of students, emotions and attitudes that often change, as well as impaired function of the senses of sight and hearing (eyes and ears) while factors that come from outside or external are family environmental factors,community and school. The purpose of this study was to determine emotional stability, academic stress, characteristics such as gender in SMAN 3 Tangerang Regency. Methods: Correlation description design with Cross Sectional approach. The population in this study were students of class XI and XII of IPS SMAN 3 Tangerang Regency as many as 380 students, the number of samples was 195 students. The technique used is Stratified Random Sampling. Collecting data using a questionnaire of emotional stability and academic stress. Results: : In this study using the Chi-Square table test with a p-value smaller than 0.05 which indicates that Ho is rejected and Ha is accepted so that it can be stated that there is a significant relationship between adolescent emotional stability and academic stress in students at SMAN 3 District Tangerang. Conclusions: Based on this research, it is expected that schools, parents, and students' environment will pay more attention to students and help to manage the stress experienced by students due to academic demands.